Vocational Teacher Educators’ Role Identity: A Case Study in Malta - Said, Alison (Qualitative Sociology Review, 2022)
This paper gains a deeper understanding of the professional role identities of vocational teacher educators (VTEs) when compared with mainstream teacher educators (MTEs) in Malta. It is framed using identity theory from the structural symbolic interactionism perspective (Burke and Stets 2009). Data were collected through semi-structured interviews, adopting thematic analysis. Findings show that VTEs and MTEs underpin their teaching differently, influenced by the perceptions they have about their professional role identities. There is no “one size fits all” solution for each country, yet this study contributes to a field with a limited research base and offers new insights to identity theory.